The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1439-0264.2007.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

The Right Coronary Artery is Absent in the Chinchilla (Chinchilla lanigera)

Abstract: A total of 10 adult, healthy, male chinchillas (Chinchilla lanigera) were used to investigate the origin, course, and termination of the coronary arteries. Coloured latex was injected into the carotid arteries following conventional anatomical applications. In all the chinchillas examined, the left coronary artery was the single coronary artery. The right coronary artery was missing. Additionally, a small vessel originating from the cranial border of the aorta was observed in one chinchilla. The left coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
(41 reference statements)
1
15
2
1
Order By: Relevance
“…Similar observations were made in ruminants (Nickel et al 1981;Barone 1996), reo deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), European bison (Kupczyńska et al 2015) and Angora rabbit (Bahar et al 2007). However, in dog was described the additional right coronary artery (Bezuidenhout 2013) while in chinchilla the right coronary artery was absent Ozdemir et al (2008). In our study, the right coronary artery terminated primarily as small branches on the atrial surface of the heart.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Similar observations were made in ruminants (Nickel et al 1981;Barone 1996), reo deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), European bison (Kupczyńska et al 2015) and Angora rabbit (Bahar et al 2007). However, in dog was described the additional right coronary artery (Bezuidenhout 2013) while in chinchilla the right coronary artery was absent Ozdemir et al (2008). In our study, the right coronary artery terminated primarily as small branches on the atrial surface of the heart.…”
Section: Discussionsupporting
confidence: 38%
“…There were a stronger paraconal interventricular branch and a weaker circumflex branch. This type of trunk morphology has also been described in ruminants (Nickel et al 1981;Barone 1996), roe deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), donkey (Ozgel et al 2004), porcupine (Atalar et al 2003), ringed seal (Smodlaka et al 2008), chinchilla (Ozdemir et al 2008), cat (Barszcz et al 2014(Barszcz et al , 2016b and European bison (Kupczyńska et al 2015). Whereas Bahar et al (2007) reported that in the Angora rabbit, the common trunk of the left coronary artery was divided into the paraconal interventricular branch, the circumflex branch and the proximal branch of the left atrium.…”
Section: Discussionmentioning
confidence: 66%
“…La predominancia de la coronaria izquierda sobre la derecha se ha demostrado en varias especies como el corzo (Frackowiak et al, 2006), el puerco espín (Atalar et al, 2003), el ratón (Yoldas et al, 2010) y en los rumiantes domésticos, donde la rama circunfleja de la arteria coronaria izquierda da origen a la arteria interventricular subsinusal (Barone). Incluso Ozdemir et al (2008) publicaron que la arteria coronaria derecha no existe en la chinchilla (Chinchilla lanígera).…”
Section: Discussionunclassified
“…The arterial vascularization of the heart was previously described [24] as well as digestive tube segments [23]. Other studies on the aortic arch in chinchilla were published later in 2004 and 2005 [2,28].…”
Section: Introductionmentioning
confidence: 99%